THE PHYSICO-CHEMICAL EVALUATION AND ENVIRONMENTAL SUSTAINABILITY OF OIL PALM DECANTER CAKE IN LUBOK ANTU, SARAWAK - ANJELINA JOFFERY KALIMUTHU, - (Universiti Malaysia Sarawak, 2022)
Oil Palm Decanter Cake (OPDC) is one of the large quantity leftovers in the oil palm mill that has been shown to have nutritional value. As a result of its widespread production, its proper disposal has become a major source of concern especially when it comes to the environmental contamination in the palm oil industry in Malaysia, with a particular focus on the palm oil mill located in Lubok Antu, Sarawak, it has been observed that Palm Oil Mill Waste (POMW) is one of the major problems that need to be taken into consideration by the mills, particularly when it comes to wastes related to OPDC, because both the disposal and the utilisation of wastes related to OPDC are not being properly disposed of and managed. It is critical that significant efforts to be made to ensure appropriate OPDC waste management in Lubok Antu Palm Oil Mill 1 (LAPOM 1) are to be done to address rising environmental concerns, hence the purpose of this project is to evaluate the physical and chemical characteristics of OPDC, besides to analyse the environmental sustainability of the potential applications of OPDC as raw material focusing on organic fertilizer and biomethane gas. In evaluating the physico-chemical (physical and chemical) analysis of OPDC for organic fertilizer and biomethane gas applications, seven analyses have been done which includes Scanning Electron Microscope (SEM), density, moisture, oil, heavy metals, Nitrogen Phosphorus Potassium (NPK), and Fourier Transmission Infrared Spectroscopy (FTIR) analysis. Besides, the inventory structure for the Carbon Dioxide Equivalent (CO2e) have been designed in order to analyse the environmental sustainability of OPDC for organic fertilizer and biomethane applications by conducting the inventory analysis. Consequently, based on all of the evaluation and analysis which have been done, biomethane gas application are selected to be the potential application of OPDC as raw material in which it emits lower CO2e compared to organic fertilizer application, besides sludge is produced upon biomethane production in which can be used as soil conditioner based on the physical and chemical characteristics that have been analysed. Biomethane is a chemical alternative to natural gas and can be used in gas distribution and transport, and electricity generation, as it has zero emissions and is interchangeable with natural gas as it can absorb methane emissions from landfills and manure production, reducing environmental methane emissions.